2022
DOI: 10.1037/dev0001354
|View full text |Cite
|
Sign up to set email alerts
|

Fine motor skills during early childhood predict visuospatial deductive reasoning in adolescence.

Abstract: Extensive evidence and theory suggest that the development of motor skills during infancy and early childhood initiates a “developmental cascade” for cognitive abilities, such as reading and math. Motor skills are closely connected with the development of spatial cognition, an ability that supports deductive reasoning. Despite the linkage between motor skills and spatial cognition, and spatial cognition with deductive reasoning, no research has explored the developmental connection between early motor skills a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Evidence based on cognitive and developmental theories suggests that early math skills are linked to future academic achievement (Cortes, Green, Barr, & Ryan, 2022;Karademir, &Akman, 2019;Dilek, Taşdemir, Konca, & Baltacı, 2020). Research further supports the position that early years are vital for developing math knowledge and skills (Ramanathan, Carter, & Wenner, 2022;Litkowski, Duncan, Logan, and Purpura, 2021;Trawick-Smith, Swaminathan, & Liu, 2016).…”
Section: Introductionmentioning
confidence: 74%
“…Evidence based on cognitive and developmental theories suggests that early math skills are linked to future academic achievement (Cortes, Green, Barr, & Ryan, 2022;Karademir, &Akman, 2019;Dilek, Taşdemir, Konca, & Baltacı, 2020). Research further supports the position that early years are vital for developing math knowledge and skills (Ramanathan, Carter, & Wenner, 2022;Litkowski, Duncan, Logan, and Purpura, 2021;Trawick-Smith, Swaminathan, & Liu, 2016).…”
Section: Introductionmentioning
confidence: 74%
“…Further, previous studies [ 19 , 22 , 23 ] showed the importance of human perception, including the weight and size of objects, as a diagnostic and monitoring tool for various health problems. This applies to violations of motor functions, cognitive, and coordination abilities of patients with neurological disorders and diseases (damages) of brain functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research and medical experience show that after a stroke, an attack of Parkinson’s disease, as well as during the early development of children, including children with Down’s syndrome and cerebral palsy, the development and restoration of the body’s motor functions play a special role [ 18 ]. Motor functions are closely related to brain functions and one of the most effective medical approaches for the development and restoration of brain function is the performance of tasks related to fine motor skills in children and adults [ 19 , 20 ]. Fine motor skills tasks include drawing, writing, playing with small objects, and solving three-dimensional puzzles with different geometric shapes, such as sphere, cylinder, tetrahedron, and cube, in various weights, depending on the patient age and health issues.…”
Section: Background Of Object Perception In the Fields Of Cognition A...mentioning
confidence: 99%
“…In preverbal children, the development of motor skills is closely connected with the development of spatial cognition (Cortes et al, 2022; Dilks et al, 2022; Newcome, 2019; Vasileyva & Lourenco, 2012), and appears promising as an early life candidate of study. Of relevance here, impaired motor learning has been proposed as a core symptom of ASD (see Bo et al, 2016), and the question therefore becomes how well motor learning impairments may predict scene construction in ASD.…”
Section: Future Directionsmentioning
confidence: 99%